2023
DOI: 10.3390/jcm12216873
|View full text |Cite
|
Sign up to set email alerts
|

The RAAS Goodfellas in Cardiovascular System

Ilaria Caputo,
Giovanni Bertoldi,
Giulia Driussi
et al.

Abstract: In the last two decades, the study of the renin–angiotensin–aldosterone system (RAAS) has revealed a counterregulatory protective axis. This protective arm is characterized by ACE2/Ang 1-7/MasR and Ang 1-9 that largely counteracts the classic arm of the RAAS mediated by ACE/Ang II/AT1R/aldosterone and plays an important role in the prevention of inflammation, oxidative stress, hypertension, and cardiovascular remodeling. A growing body of evidence suggests that enhancement of this counterregulatory arm of RAAS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 128 publications
0
5
0
Order By: Relevance
“…The RAS has been shown to elevate ROS levels and plays a role in the development of hypertension caused by IH and SAS [80][81][82][83]. Angiotensin II (ANG II), the primary hormone responsible for the actions of RAS, affects both the peripheral and central systems, which can increase sympathetic activity and play a role in the development of hypertension [84].…”
Section: Renin-angiotensin System (Ras)mentioning
confidence: 99%
“…The RAS has been shown to elevate ROS levels and plays a role in the development of hypertension caused by IH and SAS [80][81][82][83]. Angiotensin II (ANG II), the primary hormone responsible for the actions of RAS, affects both the peripheral and central systems, which can increase sympathetic activity and play a role in the development of hypertension [84].…”
Section: Renin-angiotensin System (Ras)mentioning
confidence: 99%
“…It is well known that Ang II can bind two different receptors, AT1R and AT2R, the former being responsible for the deleterious effects of the renin-angiotensin system (RAS) and the latter mediating opposite effects. In addition, Ang 1-7 binds the Mas receptor exerting anti-inflammatory, antithrombotic, antiproliferative, and vasodilatory effects, and the ACE2-Ang 1-7 pathway is considered the counter-regulatory arm of RAS [5].…”
Section: Mas Receptor and At1rmentioning
confidence: 99%
“…Gitelman and Bartter Syndromes (GS/BS) are two rare genetic tubulopathies characterized by metabolic alkalosis, hypokalemia (hypomagnesemia in GS), hyperactivation of RAS, and high Ang II and aldosterone level, yet normo/hypotension [9,10] and activation of the RAS counter-regulatory arm with increased ACE2 and Ang 1-7 levels, resulting in antiatherosclerotic, antiproliferative, and antifibrotic effects [5,11]. The Ang II-AT1R signaling pathway is indeed blunted in these patients, as they show a downregulation of the RhoA-Rho kinase (ROCK) pathway due to a higher expression of the Regulator of G-protein Signaling 2 that regulates the Ang II G protein coupled receptor signaling.…”
Section: Gitelman and Bartter Syndromes: Two "In Vivo" Models Of Sars...mentioning
confidence: 99%
See 1 more Smart Citation
“…RAAS inhibitors include angiotensin-converting enzyme inhibitors (ACEi), angiotensin II receptor antagonists (ARBs), aldosterone antagonists, and direct renin inhibitors ( 20 ). Recent studies have found that RAAS inhibitors significantly slow the progression of a wide range of diseases, including hypertension, myocardial remodeling after acute myocardial infarction, acute and chronic heart failure, and renal insufficiency, improving the prognosis of patients ( 21 , 22 ). RAAS inhibitors dilate the glomerular outgoing and incoming small arteries to different degrees, and reduce the glomerular intraglomerular pressure leading to a decrease in urinary protein ( 23 ).…”
Section: Introductionmentioning
confidence: 99%